Distribution Route Optimization Using the Nearest Neighbor Method and the Tabu Search Algorithm at PT. XYZ - syakri lasau; Idham Halid Lahay; Rahmat Deddy Riyanto Dako; Jamal Darusalam Giu; Amirudin Yunus Dako; Syahrir Abdussamad (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
PT. Sinar Kristal Nusantara currently only relies on driver experience in determining distribution routes without special studies, which causes delays in the delivery of crystal ice products due to irregular distribution flow. This study aims to determine the optimal distribution route with the shortest distance to make deliveries more efficient and timely. The methods used are Nearest Neighbor and Tabu Search algorithm. The process starts by classifying the initial route using Saving Matrix, then determining the optimal route through Nearest Neighbor and Tabu Search. The results showed that this method resulted in a total mileage of 31.05 km with a travel time of 37.26 minutes, more efficient than the current route which reached 63.90 km with a time of 75 minutes. Tabu Search proved to be a superior optimization method because it produced a shorter route than using Nearest Neighbor alone. In conclusion, the combination of Nearest Neighbor and Tabu Search can improve the efficiency of crystal ice distribution at PT. Sinar Kristal Nusantara.